Ibn Sina's Marriage Concept: Integration of Islamic Philosophy and Modern Psychology - Wiwin Luqna Hunaida; Dhuha Hadiyansyah (Journal Intellectual Sufism Research (JISR), 2022)
This qualitative research aims at finding the concept of marriage according to Ibn Sina and the synthesis of the concept of marriage by him with the concept of marriage in John Bradshaw's modern psychology through number of books they wrote. After examining a number of sources, the authors found that there are many areas of discussions that that Ibn Sina missed but were scrutinized in detail by John Bradshaw. This study concludes that interdisciplinary studies are needed as an effort to complement both Islamic knowledge and modern studies in order to produce an integral discussion